All-metallic nanorattles consisting of a Pt core and a mesoporous PtPd shell for enhanced electrocatalysis. (9th September 2019) - Wang, Hongjing; Yin, Shuli; Li, Chunjie; Deng, Kai; Xu, You; Wang, Ziqiang; Li, Xiaonian; Xue, Hairong; Wang, Liang
Abstract: The fabrication of nanorattles with controllable compositions and structures is very important for catalytic applications. Herein, we propose a facile method for synthesis of very unique all-metallic nanorattle consisting of a Pt core and a mesoporous PtPd shell (named Pt@mPtPd). Owing to its spatially and locally separated active inner Pt core and mesoporous PtPd shell, the Pt@mPtPd nanorattle shows the enhanced performance for oxygen reduction reaction. The newly designed Pt@mPtPd nanorattle is quite different from traditional nanorattles with porous carbon and silica shell in its catalytically functional mesoporous metallic shell. The proposed facile method is highly valuable for the design of all-metallic nanorattle with controllable compositions and desired functions.